2009
DOI: 10.1016/j.mechmachtheory.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Tensegrity frameworks: Dynamic analysis review and open problems

Abstract: The main objective of this paper is twofold. First, to conclude the overview about tensegrity frameworks, started by the same authors in a previous work, covering the most important dynamic aspects of such structures. Here, the most common approaches to tensegrity dynamic modeling used so far are presented, giving the most important results about their dynamic behavior under external action.Also, the main underlying problems are identified which allow the authors to give a clear picture of the main research li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 87 publications
(147 reference statements)
0
29
0
Order By: Relevance
“…Tensegrities are spatial, reticulated and lightweight structures that are composed of struts and cables. Stability is provided by the self-stress state in tensioned and compressed elements (Juan and Mirats Tur, 2008;Mirats Tur and Hernàndez Juan, 2009). The tensegrity concept has applications in fields such as sculpture, architecture, aerospace engineering, civil engineering, marine engineering and biology .…”
Section: Introductionmentioning
confidence: 99%
“…Tensegrities are spatial, reticulated and lightweight structures that are composed of struts and cables. Stability is provided by the self-stress state in tensioned and compressed elements (Juan and Mirats Tur, 2008;Mirats Tur and Hernàndez Juan, 2009). The tensegrity concept has applications in fields such as sculpture, architecture, aerospace engineering, civil engineering, marine engineering and biology .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, deployable structures were widely investigated in the late 20th century. The deployable concept was coined by Fuller in the early 1960s [2] and was initially used to the movable theater in the 1960s by Pienro, an architect from Spain [3,4]. From the viewpoint of mechanism theory, the deployable structures were probed as early as the 19th century by Sarrus, Bricard, and in the early 20th century by Bennett et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies found in the literature investigated form-finding [8][9][10][11][12] and design characteristics of tensegrity structures [13][14][15][16]. Statics and dynamics of simple tensegrity modules have also been investigated [17][18][19].…”
Section: Introductionmentioning
confidence: 99%